Experimentally-based analytical model of deep-submicron LDD pMOSFET’s in a Bi-MOS hybrid-mode environment - Rofail, Samir S. (2009)
The hybrid-mode operation of deep-submicron LDD pMOSFET’s has been investigated experimentally. Based on the experimental results, analytical models for the threshold voltage, the device currents, the transconductance, and the output conductance were derived. The various current components in this mode of operation were extracted and identified. The effects of independently biasing the source, drain, gate, and body potentials on the device currents and parameters were examined. The bodyinduced-barrier-lowering (BIBL) effect, which is one of the VSB effects and introduced for the first time, has been used to account for the changes in both the threshold voltage and the device currents caused by the forward source-body bias.